Impact of an antimicrobial stewardship program on healthcare-associated Clostridium difficile rates at a community-based teaching hospital. Issue 4 (July 2018) - Moffa, Matthew A; Walsh, Thomas L; Tang, Amy; Bremmer, Derek N
We conducted a pre-intervention/post-intervention study to assess the rate of healthcare-associated Clostridium difficile infections (HA-CDI) before and after the implementation of an antimicrobial stewardship program (ASP). Upon implementation of our ASP, the usage of targeted antimicrobials, including ceftriaxone, clindamycin, fluoroquinolones and carbapenem antibiotics, were significantly reduced. There was also a significant reduction in HA-CDI/1000 patient-days following ASP implementation (0.84 vs. 0.28; P = 0.035).